Sentimen Analisis Pembatalan Indonesia Menjadi Tuan Rumah Piala Dunia U-20 Menggunakan Metode Naïve Bayes - Rozaq Sulastiyono; Agus Setiawan; Setiya Nugroho (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Football is the most popular sport in the world, including Indonesia. Several football tournaments have been postponed due to Covid-19, including the U-20 World Cup which will be held this year in Indonesia. However, the tournament was rejected by several parties who did not want one of the participating countries to take part in the tournament. As a result, the FIFA federation canceled Indonesia as the host for the 2023 U-20 World Cup. The polemic that has occurred in the last few weeks has generated many opinions and opinions from social media users, one of which is Twitter. This study focuses on classifying opinions from tweets on Twitter regarding the cancellation of Indonesia from hosting the U-20 World Cup. This sentiment classification uses the Lexicon Based method to determine positive, negative and neutral sentiments, classification uses the Multinomial Naïve Bayes method for calculating accuracy with the Confusion Matrix. Based on the system built, an accuracy of 85% is obtained with a precision of 85%, a recall of 85%, and an f1-score value of 83%.